NUMERICAL INTEGRATION IN VOLUME CALCULATION OF IRREGULAR ANTICLINES - Tomislav Malvić; Rajna Rajić; Petra Slavinić; Kristina Novak Zelenika (Rudarsko-geološko-naftni Zbornik, 2014)
The volume of geological structures is often calculated by using the definite integral. Though in some cases the integral can be solved analytically, in practice we usually approximate its value by numerical integration techniques. The application of definite integral in volume calculation is illustrated by two examples. The volume of Mount Fuji, the world-known “conic” geomorphological structure, is calculated by analytical integration. Two basic numerical integration methods, that is, the trapezoidal and Simpson’s rule are applied to subsurface hydrocarbon reservoir volume calculation, where irregular anticline is approximated by a frustum of a right circular cone.